2022
DOI: 10.3389/fcimb.2022.905906
|View full text |Cite
|
Sign up to set email alerts
|

The giant E3 ligase HUWE1 is linked to tumorigenesis, spermatogenesis, intellectual disability, and inflammatory diseases

Abstract: E3 ubiquitin ligases determine the substrate specificity and catalyze the ubiquitination of lysine residues. HUWE1 is a catalytic HECT domain-containing giant E3 ligase that contains a substrate-binding ring structure, and mediates the ubiquitination of more than 40 diverse substrates. HUWE1 serves as a central node in cellular stress responses, cell growth and death, signal transduction, etc. The expanding atlas of HUWE1 substrates presents a major challenge for the potential therapeutic application of HUWE1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…HUWE1 has been reported to regulate a diverse and growing number of cellular pathways through the targeted degradation of structurally diverse proteins (Giles and Grill, 2020; Qi et al, 2022). In order to characterize the mechanisms HUWE1 utilizes to enable such plasticity towards its substrates, we performed quantitative and deep whole cell proteomics to identify proteins whose steady-state abundance is elevated upon HUWE1 loss of function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HUWE1 has been reported to regulate a diverse and growing number of cellular pathways through the targeted degradation of structurally diverse proteins (Giles and Grill, 2020; Qi et al, 2022). In order to characterize the mechanisms HUWE1 utilizes to enable such plasticity towards its substrates, we performed quantitative and deep whole cell proteomics to identify proteins whose steady-state abundance is elevated upon HUWE1 loss of function.…”
Section: Resultsmentioning
confidence: 99%
“…HUWE1 is an enigmatic ubiquitin ligase that has been implicated to regulate numerous cellular pathways including DNA repair, transcription, proliferation, apoptosis, and cell signaling (Qi et al, 2022). Further, HUWE1 has been described to both promote and restrict tumorigenesis, as well as play critical roles in neurodevelopmental pathways (Adhikary et al, 2005; Forget et al, 2014; Giles and Grill, 2020; Gong et al, 2020; Hao et al, 2012; Inoue et al, 2013; King et al, 2016; Kunz et al, 2020; Myant et al, 2017; Opperman et al, 2017; Peter et al, 2014; Yang et al, 2018; Zhao et al, 2009; Zhao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of substrates that can be ubiquitinated by HUWEI1 has exceeded 40. It is closely related to cell stress responses, cell statue, signal transduction, inflammasome activation, and other cellular processes [ 168 ]. Comprehensive molecular studies have shown that HUWE1 can target various substrates, including c-Myc [ 169 ].…”
Section: Other E3 Ligasesmentioning
confidence: 99%